1991
DOI: 10.1210/endo-128-6-3219
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Carbonic Anhydrase II by Androgen and Estrogen in Dorsal and Lateral Prostate of the Rat*

Abstract: Hormone regulation of carbonic anhydrase II (CA II) was studied in rat dorsal and lateral prostate. CA II is a major soluble protein in these accessory sex glands. The immunoelectronmicroscopy showed that CA II is expressed in their epithelial cells only. For studies on hormone regulation, adult male rats were castrated for 2 or 7 days. Groups of 7-day castrates and normal rats were treated daily either with testosterone or 17-beta-estradiol for 6 days and 2-day castrates for 1 day. CA II protein was analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Further investigations are required to understand their androgen‐responsive mechanisms. The CA2 expression exemplifies the differential androgen dependency of the transcription between lobes, as previously reported (Harkonen et al, 1991), which showed that CA2 mRNA expression was up‐regulated by androgen in the LP, whereas it was down‐regulated in the DP in SD rats. In the present study, there were comparable responses in CA2 mRNA in the LP but no significant changes in the DP, which may be because of differences in androgen dosages or the mRNA quantification methods.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Further investigations are required to understand their androgen‐responsive mechanisms. The CA2 expression exemplifies the differential androgen dependency of the transcription between lobes, as previously reported (Harkonen et al, 1991), which showed that CA2 mRNA expression was up‐regulated by androgen in the LP, whereas it was down‐regulated in the DP in SD rats. In the present study, there were comparable responses in CA2 mRNA in the LP but no significant changes in the DP, which may be because of differences in androgen dosages or the mRNA quantification methods.…”
Section: Discussionsupporting
confidence: 83%
“…The differential responses of CA2 to androgen suggest the lobe-specific function of this protein. Estrogen and the other hormone may be also involved in the androgen regulation of CA2 (Harkonen et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…14 The regulatory mechanisms are complex, however, because androgens induce CA II expression in some organs and inhibit it in others. 10 Expression of CA II has recently been found to be common in the endothelial cells of highgrade oligodendrogliomas and diffuse infiltrating astrocytomas. 8 Carbonic anhydrase II positivity also correlated with tumor grade and poor prognosis; CA II reactivity was highest in high-grade astrocytomas, which are vascularized tumors containing necrotic areas.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat, prolactin receptor is present in both dorsal (DP) and lateral (LP) prostate [47]. This fact is important because the hormone responsiveness of distinct rat prostate lobes has been shown to be different [48,49] and the dorsal and lateral parts of rat prostate are considered most sensitive to prolactin [20,50]. Prolactin serum levels increase with age and are associated with normal development and growth of the prostate and with zinc and citrate accumulation in the prostate [51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%